The Development of Swingtie Ball Media for Baseball Game Learning Aids for Elementary School Students - Achmad, Fairuz Yosmaral; Soenyoto, Tommy; Irawan, Fajar Awang (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This study aimed to establish an aids in process of learning hit technique. This research was the development research with research and development methods. Subjects in this research were material, learning, media experts and students of 30 people for small scale trial and 110 people for big scale trial. Instrument used to collect data were interview. Observation, questionnaire and documentation. Small scale trial of material expert gave assessment score in average of 4.47 or 89% in Ã¢â‚¬Å“very good categoryÃ¢â‚¬Â. Big scale trial gave average score of 4.60 or 92% in Ã¢â‚¬Å“very goodÃ¢â‚¬Â category. Small scale trial of learning expert gave average score of 4.20 or 84% in Ã¢â‚¬Å“very goodÃ¢â‚¬Â category. Big scale trial gave average score of 4.53% or 91% in Ã¢â‚¬Å“very goodÃ¢â‚¬Â category. Small scale trial of media expert gave average score of 4.07 or 81% in Ã¢â‚¬Å“very goodÃ¢â‚¬Â category. Big scale trial gave average score of 4.27 or 85% in Ã¢â‚¬Å“very goodÃ¢â‚¬Â category. Product trial in small scale obtained average score of 0.89 or 89% in Ã¢â‚¬Å“very goodÃ¢â‚¬Â category. Product trial in big scale obtained average score of 0.88 or 88% in Ã¢â‚¬Å“very goodÃ¢â‚¬Â category. The conclusion in this research is that, the product named swingtie ball is effective and worthy to use for learning hit technique in baseball game for elementary school students.